Complements and Substitutes between Chatbots and Humans: Corporate Perspectives - Tatcha Sudtasan; Pantaree Pitivaranun (International Telecommunications Society (ITS), 2019)
The aim of this study is to determine the perceptions of business on the abilities of human labor and robots or Artificial Intelligence, where different types of labors, human and AI, suit different types of job duties. Chatbot is selected as a case because it has passed the introduction stage of its life cycle. It is now widely accepted and has become one of the major trends in business and corporate utilization among advanced countries such as Japan, China and USA. The study focuses on service sector in the position of customer service, call center, and lecturer. The results show that corporates perceive Chatbot as potential opportunity to work as receptionist, operator, call center, customer service staff and lecturer. The results imply that with only the factors of efficiency, productivity, cost of time, wage, and cost of production there are going to be difficulties for human labors to work in these duties. Government, therefore, should revamp the system and scheme of education in Thailand which is support in both worker skills and working skills with more complex, creative, critical, and service orientation in order to differentiate and maintain balances between the uses of advanced technologies and human jobs.
Keywords: 330; Human worker; chatbot; corporate perspectives; complements; substitutes